Evaluation of the Care Costs for Non-Communicable Diseases Incurred by Patients in the Greater Tunis Area (Indian Journal of Public Health Research & Development, 2023)
Objectives: The objective of this study was to estimate the costs and expenses incurred by patients for themanagement of non-communicable diseases (NCDs).Methods: The study was carried out in 7 Basic Health Centers (BHCs) distributed all over Greater Tunis and wasconducted using a new tool: the COPAQ.Results: According to the survey, the direct medical cost was estimated at 127 ± 204.4 TND, while the indirect costwas estimated at 21.58 ± 39.07 TND and the patient spend a total cost of about 149.1 ± 212.2 TND. Compared tothe guaranteed interprofessional minimum salary, which is set at 378.560 TND, and to the monthly income of theinterviewed patients, which varies between 300-600 TND, the total cost of chronic diseases seemed to be enormousand not affordable for most patients.Conclusions: The Tunisian state should take into consideration the incurred expenses and move towardspreventive strategies to decrease the spread of these diseases and thus reduce their costs
Keywords: Direct costs, indirect costs, non-communicable diseases, COPAQ